Tinjauan Ekonomi Islam Terhadap Manajemen Keuangan Pada Industri Rumahan Jilbab Muizz Collection - Farhana, Nora Farita; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2018)
Islam has always urged adherents working and improving the work ethic. It encourages its adherents to Islam to plunge into entrepreneurs (entrepreneurs). One of the types of businesses that are thriving in Indonesia is small and medium scale business (UMKM). One of the Small Medium Enterprises that started developing right now is "Muiz Collection" engaged in the field of convection (hijab). This study used a qualitative approach. Type of research is the research field. In this study using primary and secondary data sources. Data collection techniques are obtained by means of interviews, observation, and documentation. Financial management in "Muiz Collection" consists of 3 mechanism: collection of funds obtained from personal funds and loans,use of funds to finance all expenditure. Business principles relating to sharia provision are always firmly and used as a reference for action by Muiz Collection so that Muiz Collection can be categorized as a home industry that applies the principles of islamiceconomics.